The Influence of Perceived Ease of Use and Perceived Benefit on QRIS User Satisfaction in Pontianak City - Kartika, Kartika; Fachri, Helman (SAINTIS Publishing, 2025)
The adoption of QRIS in Pontianak has continued to grow in line with changing payment patterns among the community. This study aims to analyze the influence of perceived ease of use and perceived benefit on QRIS user satisfaction. A quantitative method with an associative design was employed, involving 100 respondents selected through purposive sampling. Data were collected using a 5-point Likert scale questionnaire and analyzed through validity and reliability testing, classical assumption tests, and multiple linear regression analysis. The results indicate that all instruments were valid and reliable, the data were normally distributed, and no multicollinearity was detected. Regression analysis produced a correlation coefficient (R) of 0.708 and a coefficient of determination (R²) of 0.502. The F-test confirmed that both independent variables simultaneously have a significant effect on satisfaction (F = 48.806; p 0.001). Partial tests showed that perceived ease of use (β = 0.401; p 0.001) and perceived benefit (β = 0.274; p = 0.002) each exert a significant positive influence. In conclusion, QRIS user satisfaction is determined by the perceived ease of use and perceived benefits. The practical implication emphasizes the need for service providers to continuously improve accessibility, security, and the added value of transactions. Future research is recommended to incorporate additional variables such as trust or service quality and to extend the scope of study areas for broader generalization.